Environmental sensitivity of GaN nanofins grown by selective area molecular beam epitaxy. (23rd April 2023) - Pantle, Florian; Wörle, Simon; Karlinger, Monika; Rauh, Felix; Kraut, Max; Stutzmann, Martin
Abstract: Nanostructures exhibit a large surface-to-volume ratio, which makes them sensitive to their ambient conditions. In particular, GaN nanowires and nanofins react to their environment as adsorbates influence their (opto-) electronic properties. Charge transfer between the semiconductor surface and adsorbed species changes the surface band bending of the nanostructures, and the adsorbates can alter the rate of non-radiative recombination in GaN. Despite the importance of these interactions with the ambient environment, the detailed adsorption mechanisms are still not fully understood. In this article, we present a systematic study concerning the environmental sensitivity of the electrical conductivity of GaN nanofins. We identify oxygen- and water-based adsorbates to be responsible for a quenching of the electrical current through GaN nanofins due to an increased surface band bending. Complementary contact potential difference measurements in controlled atmospheres on bulk m - and c -plane GaN reveal additional complexity with regard to water adsorption, for which surface dipoles might play an important role besides an increased surface depletion width. The sensitive reaction of the electrical parameters to the environment and surface condition underlines the necessity of a reproducible pre-treatment and/or surface passivation. The presented results help to further understand the complex adsorption mechanisms at GaN surfaces. Due to the sensitivity of the nanofin conductivity on the environment, such structures could perform well as sensing devices.